THE REPRESENTATION OF BABUR IN THE WRITINGS OF GERMAN AUTHOR FRITZ WURTLE - Anarkulova Zubayda Fayzullo qizi; Uzswlu Zoirova Sevinch (Web of Journals Publishing, 2024)
This article provides information about the work of the German writer Fritz Wurtle, The Prince of Andijan. In this, Zahiriddin Muhammad Babur's life path and the difficulties he experienced during his life are presented. This article describes the life path of Andijan prince Zahiriddin Muhammad Babur.
Keywords: Prince, poet, political activities, century.